A One-Step Sample Concentration, Purification and Albumin Depletion Method for Urinary Proteomics - Vaezzadeh, Ali R. (2010)
Workflows in urinary proteomics studies are often complex and require many steps to enrich, purify, deplete and separate the complex mixture. Many of these methods are laborious, time-consuming and have the potential for error. Although individual steps of these methods have been previously studied, their downstream compatibilities with fractionation technologies such as Off-Gel electrophoresis have not been investigated. We developed a One-Step sample preparation workflow that simultaneously i) concentrates proteins, ii) purifies by removing salts and other low molecular weight compounds and iii) depletes (albumin) from urine samples. This simple and robust workflow can be multiplexed and is compatible with a diverse range of downstream multidimensional separation technologies. Additionally, due to its high reproducibility and flexibility in processing samples with different volumes and concentrations, it has the potential to be used for standardization of urinary proteomics studies, as well as for studying other body fluids of similar complexity.